1995
DOI: 10.2307/1940626
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Significance of Egg Size in the European Starling: Experimental Tests

Abstract: Reproductive success in relation to egg size was studied in European Starlings (Sturnus vulgaris) by swapping whole clutches between nests at the stare of the incubation period. Egg size did not reflect parental quality as no measure of reproductive success was correlated with the foster mothers' mean egg size. There was a significant positive relationship between the mean size of the cross—fostered egg and the subsequent mean size of hatchlings. The mean size of cross—fostered eggs did not affect hatching suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 33 publications
10
57
0
Order By: Relevance
“…But we did not find correlation between egg size and nestling survival, like many other authors (e.g. Jarvinen & Ylimaunu 1984, Magrath 1992, Smith et al 1995and Styrsky et al 1999. Schifferli (1973) found such a correlation only for the second brood, Ojanen (1983) only in some years, and Smith & Bruun (1998) in a poorer habitat.…”
Section: Effect Of Egg Size On Nestling Survivalsupporting
confidence: 63%
See 2 more Smart Citations
“…But we did not find correlation between egg size and nestling survival, like many other authors (e.g. Jarvinen & Ylimaunu 1984, Magrath 1992, Smith et al 1995and Styrsky et al 1999. Schifferli (1973) found such a correlation only for the second brood, Ojanen (1983) only in some years, and Smith & Bruun (1998) in a poorer habitat.…”
Section: Effect Of Egg Size On Nestling Survivalsupporting
confidence: 63%
“…Magrath 1992, Nilsson & Svensson 1993, Smith et al 1995, Smith & Bruun 1998. Only Ricklefs (1984) did not find any relationship between egg size and nestling growth.…”
Section: The Effect Of Egg Size Per Sementioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, he suggested that the most important effect of variation in egg size might be in determining the probability of offspring survival in the first few days after hatching (Williams 1994). Large eggs appear to have an advantage in harsh environments (Smith et al 1995;Fox and Czesak 2000). On the Tibetan Plateau, elevation affects the breeding ecology of birds (Lu et al 2007(Lu et al , 2008(Lu et al , 2010Du et al 2012Du et al , 2014 through the strong effects of temperature and rainfall, which also affect plant distribution and food availability.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of low temperature and less precipitation would adversely affect the survival of the nestlings. The Black Redstarts adopted the strategy of laying larger eggs, which would improve the fitness of the nestlings under the harsh environment to recover the costs conferred by the environment (Smith et al 1995;Fox and Czesak 2000). Therefore, because large eggs are produced in response to the harsher environment, a reduction in clutch size becomes a more favorable strategy, which can increase the input of each egg, whereas reducing the number of offspring can ensure that the offspring have a higher survival rate for future generations.…”
Section: Discussionmentioning
confidence: 99%